A qualitative study exploring midwives' perceptions and knowledge of maternal obesity: Reflecting on their experiences of providing healthy eating and weight management advice to pregnant women. Issue 2 (25th September 2017) - McCann, Mary T.; Newson, Lisa; Burden, Catriona; Rooney, Jane S.; Charnley, Margaret S.; Abayomi, Julie C.
Abstract: Midwives are responsible for providing advice regarding the complex issues of healthy eating and weight management during pregnancy. This study utilised an inductive data‐driven thematic approach in order to determine midwives' perceptions, knowledge, and experiences of providing healthy eating and weight management advice to pregnant women. Semistructured interviews with 17 midwives were transcribed verbatim and data subjected to thematic analysis. The findings offer insight into the challenges facing midwives in their role trying to promote healthy eating and appropriate weight management to pregnant women. Three core themes were identified: (a) "If they eat healthily it will bring their weight down": Midwives Misunderstood; (b) "I don't think we are experienced enough": Midwives Lack Resources and Expertise; and (c) "BMI of 32 wouldn't bother me": Midwives Normalised Obesity. The midwives recognised the importance of providing healthy eating advice to pregnant women and the health risks associated with poor diet and obesity. However, they reported the normalisation of obesity in pregnant women and suggested that this, together with their high workload and lack of expertise, explained the reasons why systematic advice was not in standard antenatal care. In addition, the current lack of UK clinical guidance, and thus, possibly lack of clinical leadership are also preventing delivery of tailored advice. Implementation literature on understanding the barriers to optimal health care delivery and informing clinical practice through research evidence needs to be further investigated in this field. This study has recommendations for policy makers, commissioners, service providers, and midwives.